Length of stay after colorectal surgery in Italy: the gap between “fit for” and “actual” discharge in a prospective cohort of 4529 cases - Lorenzo Pandolfini; Duccio Conti; Piercarlo Ballo; Silvia Rollo; Alessandro Falsetto; Gian Matteo Paroli; Paolo Ciano; Michele Benedetti; Leonardo Antonio Montemurro; Giacomo Ruffo; Massimo Giuseppe Viola; Felice Borghi; et al. (Perioperative Medicine)
Abstract Background It is common to observe a gap between the day on which the discharge criteria are reached and the actual day of discharge after colorectal surgery. The aim of this study is to understand the reasons for this difference and its clinical impact on the overall length of stay (LOS). Methods All patients enrolled in the prospective iCral3 study were analyzed regarding any difference and reason between the “fit for discharge” (FFD) and “actual discharge” (AD) dates. The association between the gap and the LOS in the whole population was then assessed through a multivariate regression model including other confounding variables. Results The analysis included 4529 patients, with a median [IQR] LOS of 6 [4–8] days. The median [IQR] LOS was 6 [4–8] days in the no-gap group (3,910 patients, 86.3%), significantly lower (p < .001) than 7 [6–10] days in the gap group (619 patients, 13.7%). Among the gap reasons, the “need for postoperative rehabilitation” compared to “not willing to return home” and “social constraints” was associated with the longest LOS (9 [6.0–12.5] days, p < 0.001 vs other reasons). The existence of the gap independently determined a 2.3-day lengthening of LOS. Conclusions Among other factors, the gap between FFD and AD had an independent impact on LOS. The most frequent reasons for this gap were “not willing to return home” and “social constraint”, while the “need for postoperative rehabilitation” had the greater clinical impact.